Huli huli yan! - Wenceslao, Jose. ([s.l.] Aquarius Records)
Two responsible men trying to perfect their own craft, Olympio 'Ompong' Rocha (Dolphy) is a good provider and a very thoughtful big brother to his sister Marilou, while Sergeant Minor (Panchito) is a protective father, a single parent to his two grown-up children Raul & Lenny.
VCD
Music : Ernani Cuenco, executive producer : Emilia Santos-Blas, directed by Jose 'Pepe' Wenceslao
Dolphy, Panchito, Pinky De Leon, Eva Reyes, Larry Silva, Romy Diaz
Keywords: Comedy---feature.; Feature Family